Varicella Pneumonia in an Elderly Patient - Isidro Lumanpauw; Usman Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Varicella pneumonia is a common complication in adults, while it is a mild and self-limiting disease inchildren. Elderly patients may have severe manifestations compared to adults due to the weakening oftheir immune system in clearing the virus. Treatment with intravenous acyclovir and varicella-zosterimmunoglobulin (VZIG) offers a good prognosis, while the use of steroids is still debated. Despite standardmanagement, our case presents a fatality in an older woman with varicella pneumonia.